Анализ динамики генетико-демографических параметров (численности и половозрастных характеристик населения) малых городов и сел Восточной Украины - Федота, А.М. (Фактори експериментальної еволюції організмів, 2013)
Aims. Genetic and demographic characteristics of small rural and urban populations of Kharkov region had been investigated and their dynamics over the past twelve years had been analyzed. Methods. Different types of methods of human genetic (population and genetic-epidemiological study, estimating of marital structure and random inbreeding) and statistical analysis had been carried out. Results. The investigation has been conducted on some Eastern Ukraine populations for 1996 and 2008 has shown that the demographic process of small towns and villages has such characteristics as follows: the decreasing of effective numbers, the share lowering of the persons to be married and the share reducing of ones in the reproductive age. Conclusions. The data indicate that founded estimates of genetic and demographic parameters may be a cause of increasing of the level of inbreeding and frequencies of autosomal recessive disorders in Ukrainian populations.